1993
DOI: 10.1677/joe.0.1360497
|View full text |Cite
|
Sign up to set email alerts
|

Oxytocin-stimulated phosphoinositide hydrolysis in human myometrial cells: involvement of pertussis toxin-sensitive and -insensitive G-proteins

Abstract: Phosphoinositide hydrolysis is important in mediating the actions of oxytocin and prostaglandin (PG) F2 alpha on uterine contractions during labour. We have measured the effect of oxytocin, PGF2 alpha and other agents on the formation of inositol phosphates (IPs) in cultured human myometrial cells labelled with [3H]inositol and on changes in intracellular free Ca2+ concentration ([Ca2+]i) in cells loaded with Fura-2. Oxytocin induced the formation of [3H]IPs in a concentration-dependent manner with an EC50 (co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
82
0
3

Year Published

1994
1994
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 147 publications
(93 citation statements)
references
References 24 publications
8
82
0
3
Order By: Relevance
“…Myometrial samples were taken from the upper corpus region (termed upper segment) and from close to the cervix (termed lower uterine segment). Primary myocyte isolation and culture were essentially as described by Phaneuf et al (39). Primary myocytes were cultured with complete D-valine medium (Invitrogen), whereas the immortalized pregnant human myometrial cells (PHM1-41) and HeLa cells were cultured in Dulbecco's Glutamax II modified Eagle's medium (Sigma), supplemented with 10% fetal calf serum, penicillin (1 unit/ml), and streptomycin (1 ng/ml), and cultured in T75 flasks under standard conditions at 37°C with 5% CO2.…”
Section: Methodsmentioning
confidence: 99%
“…Myometrial samples were taken from the upper corpus region (termed upper segment) and from close to the cervix (termed lower uterine segment). Primary myocyte isolation and culture were essentially as described by Phaneuf et al (39). Primary myocytes were cultured with complete D-valine medium (Invitrogen), whereas the immortalized pregnant human myometrial cells (PHM1-41) and HeLa cells were cultured in Dulbecco's Glutamax II modified Eagle's medium (Sigma), supplemented with 10% fetal calf serum, penicillin (1 unit/ml), and streptomycin (1 ng/ml), and cultured in T75 flasks under standard conditions at 37°C with 5% CO2.…”
Section: Methodsmentioning
confidence: 99%
“…The OTR-G protein coupling in human myometrium is well described and OTR has been shown to couple with both G αq/11 and G αi to collectively regulate diverse cellular functions through complex signalling pathways [52]. In human amnion, OTR was found to initiate its pro-inflammatory signal transduction via G αi -dependent signalling [53], whilst mainly G αq/11 coupling has been found to be involved in OT-induced myometrial contractions [52].…”
Section: Inflammationmentioning
confidence: 99%
“…Accordingly, selective oxytocin analogues capable of blocking this pathway are employed in the treatment of preterm labor (9). The physiological role played by OTRs coupled to G i in myometrial cells is far less clear, although it was shown some years ago to also lead to an increase of cell contractility (10). Recently, a specific role for OTR coupled to G i has emerged in MDCK and HEK293 cells stably transfected with the human OTR, where OT inhibits cell growth in a pertussis toxin (PTx)-sensitive manner, thus suggesting a key role of OTR-G i coupling in mediating an anti-proliferative effect (11).…”
Section: S-labeled Guanosine 5-3-o-(thio) Trisphosphate ([ 35 S]gtp␥smentioning
confidence: 99%